Alternative Fuels as a Sustainable Innovation in Vehicle Fleet Across the EU–27: Diagnosis and Prospects for Development - Pangsy‑Kania, Sylwia; Biegańska, Justyna; Flouros, Floros (Comparative Economic Research. Central and Eastern Europe, 2024)
The deployment of alternatively fueled (AF) vehicles constitutes an important measure in meeting the European Union’s (EU’s) climate goals. The study aims to characterize and evaluate, in a comparative manner, the current stage of the adoption of AF passenger cars into the general (M1) passenger car fleet in the EU member states. The focal point of the study is the exploration of similarities and differences observed between the EU countries regarding the current structure of AF passenger car fleets, as well as development trends in this area. In this context, a clear scheme of “two speeds” emerges – parallel to the rapid diffusion of electric vehicles in the Nordic and Western European countries, the size and structure of the AF M1 vehicle stock remained largely unchanged in the Central‑European countries, with the dominant role of widely established liquified petroleum gas (LPG). The findings highlight the need to diversify the range of alternative fuels, which should be introduced gradually, in line with the classification proposed by the European Parliament and the Council.